ALTERNATIVE METHODS OF JUDICAL PROTECTION AND DISPUTE RESOLUTION IN ADMINISTRATIVE LAW - Gatis Litvins (European Scientific Journal, ESJ, 2013)
The administrative court is not the only and main method, instead it is just one of the methods for judicial protection and dispute resolution and the final one which solves the disputes that have not been solved by a private party and an authority within an out-of-court stage.